BIM application to enhance the quality of project management for building owners and developers - Fang, Fang (2020)
With the maturity of construction technology and the continuous updating of digital technology, e.g. Building Information Modelling (BIM), the trend to enter into a digital world is becoming widely accepted by the AEC (Architecture, Engineering and Construction) sectors. The perspective of owners and developers in project management includes cost, schedule, quality and safety. Each element shall establish corresponding goals at the initial stage of the project. The aim of this research is to establish a revised workflow for a typical construction project, which is combined with the BIM applications. In order to make all of participants understand and apply these workflows, the corresponding specifications of BIM application were established in this research, which is included the employer’s information requirements, common data environment requirements, model content, and standards. After initial investigation of the current BIM application in China and the BIM standard of BSI by UK, these specifications are considered to be very suitable for mix-used commercial project. At the same time, the new workflow for the project management will be followed and the optimization of the new workflow will be tracked in the processing of coming new project. This will be the next research in the future.